ANALISIS KONTRIBUSI SEKTOR PERTANIAN TERHADAP PENYERAPAN TENAGA KERJA DAN PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN LANDAK - B01109105, Tedy (Jurnal Curvanomic, 2015)
This study entitled: "Analysis of Agricultural Sector Contribution Against Labor Absorption And GDP in Porcupine District". This study was motivated by the agricultural sector as the sector that contributes most in GDP in the District hedgehog, but farmers still do not prosper. The purpose of research is to determine how large the contribution of the sector pertaniandi Porcupine District, knowing that dominate the agricultural sub-sector in the agricultural sector in the Porcupine District, knowing employment and government policies to develop the sub-sector in the Porcupine District 2007-2011.Penelitian used formula contribution aims to determine how large the contribution of the agricultural sub-sector in Porcupine District and analysis tools that are used to measure the sectors and sub-sectors that dominate the seed in the agricultural sector is the location quotient Â  The results showed that the agricultural sub-sector is the largest contribution to the food crops sub-sector and sub-sector plantations. Sub leading sectors that dominate the agricultural sector is the food crops sub-sector and sub-sector employment in forestry and agriculture sector is the largest of all sectors. Keywords: contribution of agriculture sector, sub-sector and employment seed.